THE INFLUENCE OF SELF-EFFICACY AND POLYA STRATEGY LEARNING ASSISTED BY MATHCITYMAP MEDIA ON PROBLEM-SOLVING ABILITY - Ilka Nur Awaliyah; Tomo Djudin; Rustam Rustam (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2026)
The purpose of this study was to determine how the application of Polya strategy learning assisted by MathCityMap media and self-efficacy impacts the mathematical problem-solving abilities of students in class VIII of SMPN 2 Pontianak on the material of Two-Variable Linear Equation Systems (SPLDV). This study is quantitative and uses a quasi-experimental design, with a post-test only control design. The research design uses a 2x2 factorial design. The population in this study were students of class VIII of SMPN 2 Pontianak. Samples were taken using random sampling techniques. Statistical tests used two-way ANOVA and independent T-test. The results of the study concluded that: (1) There are differences in students' problem-solving abilities in learning using Polya strategy learning and expository learning; (2) There is an influence on the problem-solving abilities of students who have high and low self-efficacy; (3) There is no interaction between Polya strategy learning assisted by MathCityMap and self-efficacy on students' problem-solving abilities; (4) There is no difference in problem-solving ability between students who have high self-efficacy who are involved in Polya strategy learning assisted by MathCityMap media and expository learning; (5) There is a difference in problem-solving ability between students who have low self-efficacy who are involved in Polya strategy learning assisted by MathCityMap media and those involved in expository learning